Piezochromism of cyanostilbene derivatives: a small structural alteration makes a big photophysical difference. (5th July 2021) - Zhu, Chenfei; Li, Chengjian; Wen, Li; Song, Qingbao; Wang, Kai; Lv, Chunyan; Zhang, Yujiang
Abstract : We designed two HLCT-active luminophores with high PLYQs. Under high pressure, DPMO presents better sensitivity and a smaller PL wavelength redshift than TPPA due to the high PLYQs and the strong CT state. Abstract : Piezoresponsive fluorescent materials are highly promising for applications in deformation, flaw detection and haptic sensing. Some donor–acceptor luminophores exhibit a marked redshift and high sensitivity under high pressure. However, the relationship between the intramolecular charge transfer (ICT) ability and piezochromic properties is still not clear. Herein, two novel piezochromic materials, TPPA and DPMO, have been developed. The two luminophores exhibit deep-red fluorescence with high photoluminescence quantum yields (PLQYs) as a result of the formation of a hybridized local and charge-transfer (HLCT) excited state. The fluorescent spectrum of methoxy-substituted DPMO shows a clear redshift relative to that of TPPA because the former shows stronger ICT behaviour. Under high pressure, the colour difference (spectral shift) of DPMO is clearly smaller than that of TPPA . Moreover, DPMO exhibits a much higher sensitivity (37.5 nm GPa −1 ) than TPPA (9 nm GPa −1 ). Molecular planarization is responsible for the piezochromic properties. Importantly, it is found that strong ICT behaviour can greatly improve the piezochromic sensitivity; however, it does not enhance colour differences. This research will help to design high-performance pressure-response materials in the future.